DARI KENANGAN MENUJU KESEJAHTERAAN MANFAAT REMINISCENCE THERAPY BAGI LANSIA DI GRIYA LANSIA HUSNUL KHATIMAH - Novita Permatasari; Heryanto Susilo; Salvinia Salvy Prihanta; Meria Latifatun Nisa Azira; Alfan Dwiki Candra; Rizka Arum Puspita; Rizal Aminullah (LPPM Universitas Negeri Surabaya, 2024)
This research focuses on the implementation of reminiscence therapy for the elderly at the Husnul Khatimah elderly griya in Malang Regency. In Indonesia, cases of neglect of the elderly by the family are quite high. This is evidenced by the number of neglected elderly people in the identification of PMKS (Persons with Social Welfare Problems) in East Java amounting to 173,871 people from the total population. Reminiscence therapy is very effective for the psychological healing of the elderly suffering from depressive disorders, in addition to reducing symptoms of depression, it has also been shown to increase self-esteem, life satisfaction, mental well-being and loneliness. The research method used was observation. The observation method was chosen because of its flexibility in use and can be supported by documentation. Based on the activities carried out, it shows satisfactory results, the elderly feel satisfaction with the activities received, happy for the arrival of young people who are considered as children and family and the desire of the elderly to continue to be able to gather with servants and students. Keywords: Reminiscence Therapy, Older People, Social Welfare.